(untitled) (Conferencea, 2023)
On the comprehensive development of foreign languages( English and other languages) in Uzbekistan for children and older people, the formation of a highly educated, modern-minded younger generation, as well as the creation of a comprehensive system of teaching foreign languages aimed at the further integration of the country into the world